General defense system in the plant kingdom III. - Szarka, J.; Sárdi, E.; Szarka, E.; Csilléry, G. (International Journal of Horticultural Science, 2002)
Our observations regarding the symptoms not fitting into, significantly differing from the hypersensitive defense system, which we noticed during the judgment of several plant species, symptoms provoked on several million plants have constituted a unified entity. They have provided evidence for the existence of a different plant defense system. We called this so far unknown basic response of plants to biotic effects as general defense system. This system defends them from the attack of numerous microbe species in the environment.The evolutionary intermediate phase between the general and the specific, the two defense systems is the susceptible host—pathogen relation. The vertical resistance system of plants escaping from the susceptible host—pathogen relation, based on specific hypersensitive reaction also suggested the existence of a more original, general defense system and the susceptible host—pathogen relation developed as a result of the collapse of that system.The evolutionary relation of the two defense systems is proved by the only recessive inheritance of the older general defense system and in the majority of cases dominant hereditary course of the specific defense system. In our experiences, the modifying genes of the recessive general defense system, in most cases, are behind the specific defense systems, which are known to have monogenic dominant hereditary course and react with hypersensitive tissue destruction. This seemingly striking genetic fact is explained by the following: the general defense system less dependent on environmental effects regulates much faster pathophysiological reaction than the specific resistance genes strongly dependant on environmental effects coding dominant hypersensitive reaction.The general and specific defense reactions, the processes excluding the microbes attacking plants with compacting of cell growth and tissue destruction, which mean two opposite strategies, building on and regulating each other constitute the entity of resistance to plant disease.